PROFILES OF WOMEN IN RECYCLING BUSINESS IN THE LEAST DEVELOPED STATES IN MALAYSIA â AN ALTERNATIVE ENTERPRISE? - Yaacob, Mohd Rafi (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2015)
Kelantan and Terengganu have the highest number of hardcore poors in Malaysia. Over the years entrepreneurship isÂ one of the means that has been propagated by the government to address this inherent problem. While women hithertoÂ involve in usual business activities, recently more and more women in the said states dare to jump into a new domainÂ of businesses which usually monopolized by men - recycling. This phenomenon warrants empirical research to unearthÂ pertinent questions of the inroad of female entrepreneurs in a new territory of business which overwhelmingly dominatedÂ by male entrepreneurs. Yet at present not many researchers and relevant government agencies look into recycling asÂ an alternative business but for men entrepreneurs, not women. This paper is a part of a larger study that investigatedÂ entrepreneurs and entrepreneurship in recycling business in the both states. Results of the study found that womenÂ entrepreneurs in this business are matured, married, and received full support from their families â husband andÂ children. In terms of education majority of them only study until secondary school. Highlighting women entrepreneursâÂ profiles is deemed important because interested parties including future ntrepreneurs, researchers as well as relevantÂ government agencies gain some understanding of characteristics of women entrepreneurs have made a dent in the socalledÂ male dominant business.